Environmental pollution control in Singapore: The intersection of torts, statutes, regulations and community norms - CHAN, Gary Kok Yew (Institutional Knowledge at Singapore Management University, 2019)
Singapore is a land-scarce, densely populated, urbanized and technology-driven society. Despite her image as a clean and green environment, serious challenges remain to keep environmental pollution at bay. Both private and public laws, whether based on statutes or common law, as well as a host of regulations and community norms collectively regulate environmental pollution in Singapore. Statutory provisions targeting environmental pollution rely on criminal punishment, administrative measures and also compensatory damages awarded to victims in the event of breaches of specified statutory duties. The Environmental Pollution Control Act 1999, together with the implementing subsidiary legislation, seeks to minimise or mitigate the effects of air, water and noise pollution. Government agencies adopt preventive, monitoring and/or enforcement measures backed by a plethora of statutes, regulations, international standards relating to environmental pollution. More recently, the enforcement of environmental pollution measures have extended, with the enactment of the Transboundary Haze Pollution Act 2014, to combatting environmental pollution arising from the region. Further, the common law torts of nuisance, negligence and the rule in Rylands v Fletcher exist at common law to compensate the victims for the loss suffered arising from activities resulting in environmental pollution. The goals of enhancing environmental consciousness through public education and community efforts have also been emphasised in Singapore. Nevertheless, community mediation efforts have been supplemented by the establishment of Community Disputes Resolution Tribunals to deal with complaints by neighbours of smoke, smells, and littering in the vicinity of the complainants’ place of residence.